Disentangling the invasion process of subtropical native forests of Uruguay by the exotic tree Ligustrum lucidum: establishment and dominance determinants - Brazeiro, Alejandro; Olivera, Juan; Betancourt, Alejandra; Lado, Ignacio; Romero-Pacheco, David; Haretche, Federico; Cravino, Alexandra (Springer Open, 2024)
Understanding the factors, processes, and mechanisms that regulate invasive species and their impacts is a key focus in the ecology of biological invasions. Ligustrum lucidum, a tree native to East Asia, has become an aggressive invader in subtropical and temperate forests worldwide. This study analyzes the invasion of L. lucidum in Uruguayan forests, assessing the factors that control two stages of invasion: establishment and dominance. Establishment was assessed by the presence of L. lucidum in 1,525 1 × 1 km cells, while dominance was measured by canopy cover in 5,554 cells of the same size. Generalized linear models were used to identify environmental and geographic determinants of these stages. Results show that L. lucidum established in 13.4% and dominated 1.2% of Uruguayan forests, with spatial patterns of diffusion from the S-SW region. Establishment increased with urban proximity, likely due to propagule sources from planted trees and near railways and rivers, suggesting favorable moisture conditions and corridors. Dominance was associated with smaller forest areas, fertile soils, higher altitudes, and proximity to human infrastructure, indicating that ecosystem resilience is also a factor. Invasion is expanding from the initial S-SW focus, and geographic proximity is the main predictor of establishment and dominance in the region.
Keywords: Plantas invasoras; Glossy privet; Tree invasion; Occurrence model; Dominance model